2016
DOI: 10.1111/1753-0407.12362
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dysglycaemia in rural Andhra Pradesh: 2005, 2010, and 2014

Abstract: The prevalence of dysglycemia was high at every assessment using every measurement method. Dysglycemia in this population is most likely to have risen with the rise in BMI. The decline in prevalence suggested by the secondary analyses was likely due to confounding from the different assessment methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…11 Twelve studies distinguished between urban and rural diabetes prevalence. 8,12,14,20,22,28,30,32,36,38,40,46 Fourteen studies reported only rural diabetes prevalence, [9][10]17,19,21,25,26,31,33,37,39,43,47,48 and fifteen studies reported only urban diabetes prevalence. 13,15,16,18,23,24,27,29,34,35,[41][42][43][44][45]49 One of the study had reported without mentioning urban or rural differentiation, 11 Twenty studies reported pre-diabetes (IFG).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Twelve studies distinguished between urban and rural diabetes prevalence. 8,12,14,20,22,28,30,32,36,38,40,46 Fourteen studies reported only rural diabetes prevalence, [9][10]17,19,21,25,26,31,33,37,39,43,47,48 and fifteen studies reported only urban diabetes prevalence. 13,15,16,18,23,24,27,29,34,35,[41][42][43][44][45]49 One of the study had reported without mentioning urban or rural differentiation, 11 Twenty studies reported pre-diabetes (IFG).…”
Section: Resultsmentioning
confidence: 99%
“…13,15,16,18,23,24,27,29,34,35,[41][42][43][44][45]49 One of the study had reported without mentioning urban or rural differentiation, 11 Twenty studies reported pre-diabetes (IFG). [9][10][11][12][13][14][15][16][17][18][19]23,[30][31][32][33]38,41,44,45,48 The prevalence of pre-diabetes varied across Indian states ranging from 2.4% in Meghalaya, 12 to 47.6% in Delhi. 15 Fourteen studies, [50][51][52][53][54][55][56][57][58][59]…”
Section: Resultsmentioning
confidence: 99%